Trends in Timing and Provision of Pediatric Cochlear Implant Care During COVID‐19 - Kimberley S. Noij; Emily Y. Huang; Jonathan Walsh; Francis X. Creighton; Deepa Galaiya; Stephen P. Bowditch; C. Matthew Stewart; Carolyn M. Jenks (OTO Open, 2023)
Abstract Objectives To identify trends in timing of pediatric cochlear implant (CI) care during COVID‐19. Study Design Retrospective cohort. Setting Tertiary care center. Methods Patients under 18 years of age who underwent CI between 1/1/2016 and 2/29/2020 were included in the pre‐COVID‐19 group, and patients implanted between 3/1/2020 and 12/31/2021 comprised the COVID‐19 group. Revision and sequential surgeries were excluded. Time intervals between care milestones including severe‐to‐profound hearing loss diagnosis, initial CI candidacy evaluation, and surgery were compared among groups, as were the number and type of postoperative visits. Results A total of 98 patients met criteria; 70 were implanted pre‐COVID‐19 and 28 during COVID‐19. A significant increase in the interval between CI candidacy evaluation and surgery was seen among patients with prelingual deafness during COVID‐19 compared with pre‐COVID‐19 (µ = 47.3 weeks, 95% confidence interval [CI]: 34.8‐59.9 vs µ = 20.5 weeks, 95% CI: 13.1‐27.9; p < .001). Patients in the COVID‐19 group attended fewer in‐person rehabilitation visits in the 12 months after surgery (µ = 14.9 visits, 95% CI: 9.7‐20.1 vs µ = 20.9, 95% CI: 18.1‐23.7; p = .04). Average age at implantation in the COVID‐19 group was 5.7 years (95% CI: 4.0‐7.5) versus 3.7 years in the pre‐COVID‐19 group (95% CI: 2.9‐4.6; p = .05). The time interval between hearing loss confirmation and CI surgery was on average 99.7 weeks for patients implanted during COVID‐19 (95% CI: 48.8‐150) versus 54.2 weeks for patients implanted pre‐COVID (95% CI: 39.6‐68.8), which was not a statistically significant difference (p = .1). Conclusion During the COVID‐19 pandemic patients with prelingual deafness experienced delays in care relative to patients implanted before the pandemic.